Molybdenum dosage and application timing in sweet corn (2019)
Nowadays, there is a greater offer of sweet corn hybrids with a high productive potential, shorter cycle and more intense metabolism than common corn, resulting in this crop being very demanding in terms of nutrients. The present study aimed to evaluate the effect of three levels of molybdenum (Mo) (150, 300 and 450 g ha-1), via foliar spraying, with different  application timing (E1: 100% at 15 days after  emergence - DDE; E2: 100% at 30 DDE; E3: 100% at 45 DDE; E4: 50% at 15 and 30 DDE, and E5: 33.3% at 15, 30 and 45 DDE) on the agronomic performance of sweet corn ‘SVN 9298’. There was a significant effect from the interaction of the factors on the foliar concentration of Mo, obtaining the highest value with 450 g ha-1 of Mo, applied at 45 DDE, with an increase of 1.2% in the foliar content from that observed in the plants without a Mo application. Also, the foliar concentration of nitrogen (N) was higher with the highest Mo level. The highest number of commercial ears (49,583), total productivity of ears (20,942 kg ha-1) and productivity of commercial ears (13,211 kg ha-1) were obtained with estimated levels of 316, 450 and 311 g ha-1 of Mo, respectively. Likewise, the dose that maximized grain productivity (5,055 kg ha-1), which is the most important component that defines the agronomic performance of sweet corn, was  the estimated dose of 334 g ha-1 of Mo.